Crossing disciplinary boundaries: motivations, challenges, and enablers for early career marine researchers moving from natural to social sciences. (5th December 2022) - Shellock, R J; Cvitanovic, C; Badullovich, N; Catto, D; DelBene, J A; Duggan, J; Karcher, D B; Ostwald, A; Tuohy, P
Abstract: Recent years have seen increasing calls to better document and understand the human dimensions of the marine and coastal environment and to incorporate this knowledge into decision-making. Human dimensions of the marine and coastal environment are best investigated through the application of marine social science. Individuals within marine social science are not solely "pure" social scientists, but rather are a diverse and interdisciplinary community, including many who have moved from the natural sciences to pursue a career in marine social science. This is particularly the case for early career researchers, with many moving from natural to social science earlier in their academic careers than their predecessors, and thus developing stronger interdisciplinary skills than previous generations of social scientists. In this perspective, we draw on our experiences, highlighting our main motivations for moving from natural to social science, the barriers we have faced and our top tips for early career researchers faced with similar opportunities and challenges. The ten tips include: "Work with like-minded researchers, " "Learn from and be inspired by academic heroes, " "Learn about and engage with research philosophy, positionality and reflexivity, " "Value your own skillset and perspective, " and "Be patient and kind to yourself ."